Madrasah Public Relations Strategy in Building a Positive Image Based on Islamic Values - Sudadi, Sudadi; Hifni, Hifni; Taufiqqurahman, Muhammad; Suharyatun, Suharyatun (JURNAL AL-TANZIM, 2026)
This study aims to explore madrasah public relations strategies for building a positive institutional image grounded in Islamic values in the digital era. This study used a qualitative case study design. Data were collected through in-depth interviews, participant observation, and document and digital content analysis. Data were then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results indicate that digital public relations practices at the madrasah are implemented through a structured communication system utilizing websites and social media as the primary channels. Islamic values, such as tabayyun (references), politeness of language, and publication ethics, are effectively integrated into the process of content planning, verification, and dissemination. This strategy is supported by leadership commitment, a collaborative culture among teachers and students, and adequate digital infrastructure. However, this study also identified several challenges, including limited time for administrators, variations in digital literacy, and the lack of standard procedures for managing public interactions on social media. Overall, this study confirms that integrating Islamic values into digital public relations practices not only strengthens the institution’s image but also increases public trust and credibility in the madrasah.